Management of Renal Calculus through Ayurveda: A Case Report - Dev, Kapil; Gill, Gurpreet Kaur; Yadav, C R; Singh, Bhanu Pratap (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Renal calculus is one of the most common and prevalent diseases of urinary system. It affects all countries of the world with an approximate global lifetime prevalence of 15–20%. The etiology of renal calculus is multifactorial. It bears closest resemblance to Vrikkashmari in Ayurveda. Existing non-invasive treatment modalities available in contemporary medical science have limitations in terms of efficacy and cause various adverse effects. Hence, this study is aimed to explore effective alternate in the traditional systems for satisfactory management of this disease condition. Materials and Methods: A 50-year-old female patient visited the OPD of an Ayurveda hospital with complaints of pain in the right and left flanks radiating to the lower back, burning micturition, and nausea and vomiting for 20 days. The USG report revealed about two renal calculi measuring 6 mm and 8 mm in the right and left kidneys, respectively. Ayurvedic medicines such as Shweta Parpati, Hazrulyahud Bhasma, Gokshuradi Guggulu, Chandraprabha Vati, and Varunadi Kwatha were given to the patient for 1 month. Results: A significant remission was reported in clinical symptoms as well as in imaging findings after the use of this Ayurvedic treatment protocol.